2021
DOI: 10.3389/fmed.2021.686512
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Legionella pneumophila and Aspergillus by mNGS in a Critically Ill Patient With Legionella Pneumonia After Extracorporeal Membrane Oxygenation Treatment: Case Report and Literature Review

Abstract: Legionella pneumophila can cause pneumonia, leading to severe acute respiratory distress syndrome (ARDS). Because of its harsh growth requirements, limited detection methods, and non-specific clinical manifestations, diagnosing Legionella pneumonia remains still challenging. Metagenomic next-generation sequencing (mNGS) technology has increased the rate of detection of Legionella. This study describes a patient who rapidly progressed to severe ARDS during the early stage of infection and was treated with extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Based on the mNGS, 88.2% of the PJP critically pediatric patients modified their initial antimicrobial therapy and simplify the use of antibiotics ; Trimethoprimsulfamethoxazole was not received in 82.4% of patients until the report of mNGS results. Our data and previous studies showed that mNGS is excellent for the early and precise treatment of PJP [41,42] . However, blind treatment is inappropriate only based on mNGS, since NGS technology cannot distinguish pathogens between colonization and infection.…”
Section: 5impact Of Mngs On Pjp Patients' Antimicrobial Therapysupporting
confidence: 80%
“…Based on the mNGS, 88.2% of the PJP critically pediatric patients modified their initial antimicrobial therapy and simplify the use of antibiotics ; Trimethoprimsulfamethoxazole was not received in 82.4% of patients until the report of mNGS results. Our data and previous studies showed that mNGS is excellent for the early and precise treatment of PJP [41,42] . However, blind treatment is inappropriate only based on mNGS, since NGS technology cannot distinguish pathogens between colonization and infection.…”
Section: 5impact Of Mngs On Pjp Patients' Antimicrobial Therapysupporting
confidence: 80%
“…The growth in the popularity of whole-genome sequencing techniques reflects their high diagnostic potential, and they are becoming increasingly affordable. Recent studies also demonstrate their value for microbial identification and in epidemiological studies [ 72 74 ].…”
Section: Diagnosis Of Legionnaires’ Diseasementioning
confidence: 99%
“…The specimen from bronchoalveolar lavage fluid (BALF), blood, and urine was negative for infection, as well as for specific anti-Legionella antibodies. Nevertheless, the L. mNGS identification of BALF and blood proved to be the only method that allowed for the detection of L. pneumophila [ 137 ]. Although the radiological diagnosis of pneumonia includes a chest X-ray and computed tomography [ 138 ], pneumonia due to Legionella spp.…”
Section: Diagnosis Of Legionella Diseasesmentioning
confidence: 99%